Apium graveolens Prevents Intrauterine Growth Restriction via Suppression of Antiangiogenic Factor Production - Exma Mu'tatal Hikmah; Paulus Liben; Widjiati Widjiati (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Preeclampsia is the worldwide leading cause of fetomaternal morbidity and mortality which involves the placental dysfunction. A poor placentation and formed of non-dilated spiral artery caused utero-placental circulation insufficiency, resulted in inadequate supply of nutrients and oxygen to support normal aerobic growth of the fetus. Apium graveolens or celery has been widely known as antioxidant, antiinflammation and antihypertensive with flavonoid-apigenin as main active compound. Apigenin can inhibit TNF-α, HIF-1α and nitric oxide blocking as major pathophysiological pathway of preeclampsia. This study was aimed to find how the Apium graveolens can improve intrauterine growth and its correlation with suppression of anti-angiogenic factor sFlt-1 in anti-Qa2 preeclampsia animal model. Twenty female BALB/c Mus musculus were divided into 4 groups: control, anti-Qa2 and anti-Qa2 with 500 and 1000 mg/kgBW celery herbs extract. The fetal weights and lengths, placental weights and serum sFlt-1 levels were measured and analyzed with One Way ANOVA and further tested with Least Significance Difference in 95% confidence interval. The result showed a difference between control and treatments group (p≤0.05) with 1000 mg/kgBW significantly increase intrauterine growth and decrease sFlt-1, then there is a negative correlation between intrauterine weight and serum sFlt-1. This study suggests that celery herbs extract (CHE) has an apigenin-flavonoid compound which can prevent intrauterine growth restriction (IUGR) via suppression of antiangiogenic factor production in preeclampsia mice model.